The Association Between Mycoplasma pneumoniae and Chlamydia pneumoniae, a Life-Threatening Condition in Small Children—A Case Report and a Review of the Literature - Mărginean, Cristina Oana; Meliţ, Lorena Elena; Simu, Iunius; Săsăran, Maria Oana (Frontiers in Pediatrics, 2020)
Mycoplasma pneumoniae (MP) and Chlamydia pneumoniae (CP) are two atypical pathogens that may result in mild, moderate or severe acute respiratory infections. We report the case of a 2 years and 9-month-old male child admitted with prolonged fever, dry cough and shortness of breath for which he underwent symptomatic treatment. The laboratory tests showed leukocytosis with neutrophilia, anemia and elevated inflammatory biomarkers and the thoracic radiography revealed pleural effusion raising the suspicion of inferior right pneumonia. Although we the initial evolution was favorable being treated with 3rd class cephalosporin and Oxacillin, on the 8th day of admission the fever and the acute phase reactants levels increased as well as the quantity of the pleural effusion, requiring surgical drainage. We ruled out lung tuberculosis, but we identified positive IgM for both MP and CP. Based on these findings we changed the antibiotic therapy on Levofloxacin for 10 days with favorable evolution. MP and CP are two atypical pathogen that are difficult to be diagnosed due to their slow-growing pattern. Despite their self-limiting feature, the association between them might carry a vital risk in small children, especially in the lack of a proper and timely diagnosis.